Penerapan Strategi Pemasaran, Inovasi Produk Kreatif, Dan Orientasi Pasar Terhadap Kinerja Pemasaran UMKM (Studi Pada UMKM Makanan dan Minuman di Kecamatan Lowokwaru Kota Malang) - Mas Ely Mauliyah; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the effect of marketing strategy implementation, creative product innovation, and market orientation on the marketing performance of Food and Beverage MSMEs in Lowokwaru District, Malang City. Sampling in this study used Probability Sampling, which is a random sampling technique, where each member of the population has the same opportunity to be sampled. The data analysis methods used in this study are data instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing, and determination coefficient test (Adjusted R2). Based on the research results in the multiple linear regression analysis test, it is known that the application of marketing strategy and orientation has a positive effect while creative product innovation has a negative effect and in the f test results it is known that the application of marketing strategy, creative product innovation, and market orientation simultaneously has a significant effect on the marketing performance of Eating and Drinking MSMEs in Lowokwaru District, Malang City. However, in the t test it is known that the application of marketing strategies and market orientation has a positive and significant effect on marketing performance while creative product innovation has an insignificant effect.  Keywords : Marketing Strategy Implementation, Creative Product Innovation, Market Orientation, Marketing Performance